The span of communicated ideas on corporate social responsibility (CSR) in Peru - George Angelopulo; Assim Alpaslan; Catherina Schenck (Communicare)
Since the establishment of ISO 26000, which is the international standard for social responsibility, companies around the world have increased their focus on corporate social responsibility (CSR) and on how their actions, products and services affect society. CSR is often seen as an extension of corporate communication but it is not always practised as such, and where it is, it may not always be practised according to the principles inherent in the standard. The objective of this study was to identify the span of the communicated ideas – the range of predominant beliefs – on the labour dimension of CSR in Peru. Q-methodology was used to identify four dominant perceptions on the topic. A significant finding of the study was that while there was consensus on the need to address specific issues of Peruvian labour, CSR, particularly CSR as an instrument of corporate communication, was not held up as the vehicle with which to do so.